2006
DOI: 10.1002/clc.4960290609
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fenofibrate on atherogenic dyslipidemia in hypertriglyceridemic subjects

Abstract: SummaryBackground: The metabolic syndrome (MS) is often accompanied by atherogenic dyslipidemia, which is characterized by elevated triglycerides (TG), reduced high-density lipoprotein cholesterol (HDL-C), and elevated numbers of small, dense low-density lipoprotein (LDL) particles.Hypothesis: It was hypothesized that a threshold exists for the circulating TG level needed to produce changes in LDL subclass distribution.Methods: Hypertriglyceridemic (TG ≥ 300 and < 1000 mg/dl) subjects with the MS were randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 23 publications
1
35
0
Order By: Relevance
“…We and others have hypothesized that LDL subclass pattern conversion is a threshold phenomenon such that when the TG concentration is raised or reduced beyond a threshold for an individual to switch, LDL subclass pattern conversion will occur. 12,14,56,57 It is notable that POM3 therapy was not accompanied by a change in LDL-P concentration compared with placebo. This finding is consistent with those from trials of POM3 plus simvastatin therapy, which have also shown no increase in LDL-P, but a shift in LDL subclasses (reduced IDL-P, increased large LDL-P and reduced small LDL-P), producing a net increase in mean LDL-P size.…”
Section: Discussionmentioning
confidence: 90%
“…We and others have hypothesized that LDL subclass pattern conversion is a threshold phenomenon such that when the TG concentration is raised or reduced beyond a threshold for an individual to switch, LDL subclass pattern conversion will occur. 12,14,56,57 It is notable that POM3 therapy was not accompanied by a change in LDL-P concentration compared with placebo. This finding is consistent with those from trials of POM3 plus simvastatin therapy, which have also shown no increase in LDL-P, but a shift in LDL subclasses (reduced IDL-P, increased large LDL-P and reduced small LDL-P), producing a net increase in mean LDL-P size.…”
Section: Discussionmentioning
confidence: 90%
“…16,32 If the hypothesized relationship is correct, one would expect that the on-treatment TG level would be a more important determinant of the change in LDL particle size than the degree of TG reduction. For example, a reduction in the plasma TG concentration from 5.37 to 2.94 mmol/L (475 to 260 mg/dL) would not be expected to alter LDL particle size significantly, whereas a reduction from 2.94 to 1.64 mmol/L (260 to 145 mg/dL) would produce a shift in particle size in many individuals.…”
Section: Discussionmentioning
confidence: 91%
“…16 In the present trial, most subjects showed LDL subclass pattern B (mean LDL-P size #20.5 nm) at baseline in both the P-OM3 (90.0%) and placebo (83.0%) treatment groups. The frequencies of shifts from LDL subclass pattern B to A were 19.8% in the P-OM3 group and 3.3% in the placebo group (P 5 .0002).…”
Section: Changes In Ldl Particle Size and Subclass Patternmentioning
confidence: 96%
“…However, in the present study, we did not find a relationship between HbA1c and LDL particle size or PAI-1 activity. It has been suggested that an individual threshold of fasting triglycerides exists above which LDL particles shift from large, buoyant LDL to small dense LDL particles [37,38], underscoring the importance of triglyceride levels in the determination of LDL particle size.…”
Section: Discussionmentioning
confidence: 98%